Against the Mainstream: Exploring the Nature and Role of 20th Century British Counter-Culture and Their Portrayal in Literature - Ryšanová, Michaela (Univerzita Pardubice, 2018)
The major objective of this bachelor thesis is an analysis of the British counter-culture Mod and its impact on the cultural and social scene in Britain, and on Amerika - to a lesser extent, specifically during the period of The Sixties. The thesis firstly describes the analyzed period and specifies the key changes causing a growing feeling of frustration among the youth. In the following chapter, the attention is refocused on the topic of subcultures and its impact on the British-American society. Last pages of the theoretical part are devoted to Mod, its essence and impact on the youth generation. The practical part aims to reflect the essence of Mod in the musical scene and analyzes interprets composing in symbioses with opinions and preferences of this subculture. Using musical compositions, the paper states three main reasons for emergence and popularization of Mod subculture in the British youth environment.
Proti proudu: podstata a role subkultur v Británii 20. století
Keywords: Británie; subkultury; Mod; poválečné období; šedesátá léta; období změn; odpor a frustrace; mládež; vliv hudby; Britain; subcultures; Mod; post-war period; The Sixties; period of change; resistance and frustration; youth; musical impact